Differences in personality between adolescents and older adults: What do we see and what others see? - Vukasović, Tena; Butković, Ana; Bratko, Denis (2010)
The aim of this study was to explore the differences in personality between adolescents and older adults using both self- and peer-reports at two levels of personality: domain level (Extraversion, Agreeableness, Conscientiousness, Emotional stability and Autonomy) and higher-order factor level (Alpha and Beta). Alpha is determined by Emotional stability, Agreeableness and Conscientiousness, while Beta is determined by Extravertion and Autonomy. Participants in the study were 223 adolescents (82% female) and 134 older adults (76% female). Personality was measured with FFPI (Hendriks et al., 1999) and each participant made two personality assessments. Adolescents first rated themselves and then one of their grandparents, while older adults first rated themselves and then one of their adolescent grandchildren. We tested the following hypotheses: (1) are there differences between adolescents and older adults in personality using self-reports, (2) are there differences between self-reports of adolescents and peer-reports of adolescents, (3) are there differences between self-reports of older adults and peer-reports of older adults. Results have shown that there are generational differences and differences in perception of personality depending on self- or peer-report. Self-reports show that adolescents score higher on Extravertion, Autonomy and Beta while older adults score higher on Agreeableness, Conscientiousness and Alpha. When we compared self-reports of adolescents and peer-reports of adolescents, self-reports were significantly lower for Conscientiousness, Emotional stability and Alpha. When we compared self-reports of older adults and peer-reports of older adults, self-reports were significantly higher for Agreeableness, Conscientiousness, Emotional stability, Autonomy and Alpha.
Projekt MZOS
ENG